Features of silicon and gaas on isolator technology - Новосядлий, Степан Петрович; Мельник, Любомир Васильович (Eastern-European Journal of Enterprise Technologies, 2014)
It is shown that today the main problem of SOI technology is the low reproducibility of parameters when using high-temperature technology of synthesis and detachment of mono Si layer in a hydrogen atmosphere. Physical basics of the methods for creating silicon-on-insulator (SOI) and gallium arsenide-on-insulator (GAOI) structures using different methods were considered in the paper. Major attention was paid to the «DeleCut» method (ion irradiated Deleted oxide Out), which is essentially a modification of the known «SmartCut» method and is intended to eliminate a lack of basic method. DeleCut method allows significantly reduce the annealing temperature and concentration of radiation defects in SOI and GAOI structures, decrease the thickness of the cut off layer of silicon or gallium arsenide and the transition layer between the SOI or GAOI layer and hidden oxide (oxynitride). Simultaneously, an increase in thickness uniformity of SOI or GAOI layers and dielectric (semiinsulaedr semiconductor) to several nanometers is achieved.